CORPORATE GOVERNANCE: THE GATEWAY TO A ROBUST CORPORATE FINANCIAL PERFORMANCE IN MALAYSIA - Aseh, Khairi; Kenny, Kamal; Pathmanathan, Ravindran (Archives of Business Research, 2020)
In recent years, with corporate scandals and the global financial crisis, the emerging concept of corporate governance has received increasing attention in the corporate world in these days. It is seen as a moral obligation and includes supporting the consistency of the law and showing ethical guidance. Corporate governance is seen as an important tool for the financial performance of companies, and investor investment decisions have become a more serious topic, so the relationship between corporate governance tools and measurement of financial performance has attracted researchers’ interest in the past decade mainly in developed and developing cities. In this study, we attempted to examine the impact of corporate governance on corporate financial performance in Kuala Lumpur using a sample of 215 companies on KLSE. Like previous research, firm, age, firm size, board size, CEO duality, board composition, board committees is the independent variables and their influence is to measure the financial ROA, ROE and Tobin’s q , all kinds of test is used to investigate the relationship such as descriptive analysis, Pearson moment related test and regression using first data over a period of time.